"The African Native Has No Pocket": Monetary Practices and Currency Transitions in Early Colonial Uganda - Pallaver, Karin (The International journal of African historical studies, 2015)
According to her, the idea of a "currency revolution" fails to capture the complexity of African currency changes over the longue durée.13 According to Mahir Saul, scholars have generally been too preoccupied with an opposition between types of money, without focusing on the relationship between economic process and political life.